Microbial-assisted soil chromium immobilization through zinc and iron-enriched rice husk biochar - Batool, Masooma; Rahman, Shafeeq ur; Ali, Muhammad; Nadeem, Faisal; Ashraf, Muhammad Nadeem; Harris, Muhammad; Du, Zhenjie; Khan, Waqas-ud-Din (Frontiers in Microbiology, 2022)
Soil chromium toxicity usually caused by the tannery effluent compromises the environment and causes serious health hazards. The microbial role in strengthening biochar for its soil chromium immobilization remains largely unknown. Hence, this study evaluated the effectiveness of zinc and iron-enriched rice husk biochar (ZnBC and FeBC) with microbial combinations to facilitate chromium immobilization in sandy loam soil. Methods: We performed morphological and molecular characterization of fungal (Trichoderma sp.) and bacterial (Pseudomonas fluorescence, Bacillus subtilis) species before their utilization as soil ameliorants. There were twenty-five treatments having ZnBC and FeBC @ 1.5% and 3% inoculated with bacterial and fungal isolates parallel to control in triplicates. The soil analyses were conducted in three intervals each after 20, 30, and 40 days. Results: The combination of FeBC 3%+Trichoderma viride reduced the soil DTPA-extractable chromium by 96.8% after 40 days of incubation (DAI) relative to control. Similarly, 92.81% reduction in chromium concentration was achieved through ZnBC 3%+Pseudomonas fluorescence after 40 DAI compared to control. Langmuir adsorption isotherm verified the highest chromium adsorption capacity (41.6 mg g-1) with FeBC 3% at 40 DAI. Likewise, principal component analysis (PCA) and heat map disclosed electrical conductivity-Chromium positive, while cation exchange capacity-chromium and pH-organic matter negative correlations. Conclusion: PCA suggested the ZnBC-bacterial while FeBC-fungal combinations as effective Cr(VI) immobilizers with >70% data variance at 40 DAI. Overall, the study showed that microbes + ZnBC/FeBC resulted in low pH, high OM, and CEC which ultimately played role in maximum Cr(VI) adsorption from wastewater applied to the soil.